Project management learning: Key dimensions and saliency from student experiences - Ojiako, Udechukwu; Chipulu, Maxwell; Ashleigh, Melanie; Williams, Terry (International journal of project management, 2014)
Drawing upon literature, this study seeks to understand what the key dimensions of student experiences of project management learning are and what saliences students attach to such dimensions. Data is obtained from a sample of management and engineering students studying project management across four universities in the United Kingdom. We employ multidimensional scaling to extract the salience placed by students on the key dimensions. The results of the data analysis suggest that there are six dimensions of student experiences of project management. We also find that students attach markedly different levels of salience to these dimensions based on a number of demographic factors. More specifically, in terms of salience, we found that gender had the strongest relationship while prior experience of project management had the weakest. The implications of our findings are discussed from the perspective of andragogical congruence (compatibility) in teaching and learning. •Six key student experiences dimensions project management learning are identified.•Demography greatly impacts upon different levels of student’s dimensions salience.•Implications exist on teaching and learning generic theory of project management.